Properties of CH3NH3PbX3 (X = I, Br, Cl) powders as precursors for organic/inorganic solar cells - Dimesso, Lucangelo; Hamburger, Manuel (Chemistry of materials, 2014)
CH3NH3PbX3 (X = Cl, Br, I) perovskites were prepared by a self-organization processes using different precursor solutions. The XRD analysis indicates the formation, at room temperature, of a tetragonal structure (space group I4/mcm) for X = I, of a cubic structure (space group Pm3̅m) for X = Br, and of centro-symmetric cubic structure (space group Pm3m) for X = Cl, respectively. The structural analysis revealed the formation of CH3NH3Cl as secondary phase in the Cl-containing system. The morphological investigation revealed the formation of rhombo-hexagonal dodecahedra crystallite for X = I, Br, whereas cube-like aggregates were observed for X = Cl. The thermogravimetric analysis performed in air did not reveal any loss until 250 °C for X = I and 300 °C for X = Br, respectively, whereas the differential thermal analysis (DTA) detected two endothermic thermal events (at 336 and 409 °C) for X = I and one only (379 °C) for X = Br, respectively. The infrared spectra (IR) of the powders conformed to the 3-fold symmetry of the methylammonium ion which rotates around the C-N axis. Optical absorption measurements indicated that the CH3NH3PbX3 systems behave as direct-gap semiconductors with energy band gaps of 1.53 eV for X = I, 2.20 eV for X = Br, and 3.00 eV for X = Cl, respectively, at room temperature. The direct-gap semiconductivity for X = I and X = Br was confirmed by the photoluminescence emission measurements, whereas the compound for X = Cl is inactive. I-containing powders were dissolved in an organic solvent (dimethyl-formamide, DMF). The dispersion (100-300 μL) was dropped on glassy substrates on which thick films were obtained by spin-coating and thermal treatment at 120 °C for ca. 5 min. The preparation of the layers was performed in air at room temperature.
Gesehen am 16.10.2020
Im Titel ist die Zahl 3 tiefgestellt